Pengaruh Antenatal Care, Tingkat Kecemasan, Kehamilan Beresiko Dan Jenis Persalinan Terhadap Kesiapan Fisiologis Persalinan - Gusmadewi Gusmadewi; MAYA FERNANDA DIELSA; REFLIANTO REFLIANTO (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
The physiological approach of labor and delivery is preferred for most pregnant women. Most of the research on physiological births has focused on prenatal care. A good prenatal effect on good physiological readiness too. The purpose of this study was to determine the relationship between the frequency and perception of antenatal care services, anxiety levels, pregnancy risks and types of delivery on the physiological readiness of labor. The research method is quantitative descriptive with cross sectional design. The research sample was postpartum mothers after 6 months of delivery in the working area of Puskesmas Pariaman Selatan. Analysis of research data used the chi-square test. The results of the study reported that there is a relationship between the frequency of visits and perceptions of Antenatal care services, anxiety, pregnancy risk and type of delivery with the physiological readiness of maternal delivery. Pregnant women are advised to make adequate antenatal care visits during pregnancy at least four times and encourage mothers to read a lot in order to know the physiological changes during pregnancy. This method is believed to be able to detect early when there are danger signs of pregnancy. Together with midwives and doctors, mothers can plan the process of delivering the fetus well and get positive emotional support to avoid a risky pregnancy